2019
DOI: 10.1002/cbdv.201800465
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity and Related Mechanisms of Prenylflavonoids Isolated fromMallotus conspurcatusCroizat

Abstract: Five prenylflavonoids, 6‐prenylnaringenin (1), 8‐prenylnaringenin (2), 7‐O‐methyl‐8‐prenylnaringenin (3), 7‐O‐methyl‐6‐prenylnaringenin (4), and 4′‐O‐methyl‐6‐prenylnaringenin (5), were isolated from the traditional herb Mallotus conspurcatus Croizat (Euphorbiaceae). Compounds 1–5 revealed cytotoxic activity against cervical cancer (HeLa) cells with IC50 values ranging from 10.08 to 60.16 μm by MTT method, and interestingly, these prenylflavonoids were less toxic to normal HL‐7702 cells. Furthermore, compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Some studies have reported differential impacts of 8-PN on malign and normal cells. For example, 8-PN and 6-PN displayed cytotoxic activity against the HeLa cervical cancer cells (with IC 50 values ranging from 10 to 60 μM), but were less toxic to normal HL-7702 cells [ 141 ]. Similarly, 8-PN exhibited a strong growth inhibitory effect on human colorectal carcinoma HCT-116 cells with an IC 50 value of 24 μg/mL after 48 h. However, at similar concentrations and experimental timepoints, the compound did not show any cytotoxic effect to non-cancerous colon cells (CCD-41) [ 142 ].…”
Section: Effects On Tumor Cells In Vitromentioning
confidence: 99%
“…Some studies have reported differential impacts of 8-PN on malign and normal cells. For example, 8-PN and 6-PN displayed cytotoxic activity against the HeLa cervical cancer cells (with IC 50 values ranging from 10 to 60 μM), but were less toxic to normal HL-7702 cells [ 141 ]. Similarly, 8-PN exhibited a strong growth inhibitory effect on human colorectal carcinoma HCT-116 cells with an IC 50 value of 24 μg/mL after 48 h. However, at similar concentrations and experimental timepoints, the compound did not show any cytotoxic effect to non-cancerous colon cells (CCD-41) [ 142 ].…”
Section: Effects On Tumor Cells In Vitromentioning
confidence: 99%
“…Nanoparticles of copper oxide that are usually produced from Azadirachta indica, Murraya koenigii, Tamarindus indica, Hibiscus rosasinensis and Moringa oleifera. These nanoparticles when introduced in HeLa cells showed various anti-cancer properties that include triggering apoptosis and inhibiting oxidant [46][47][48]. When HeLa cells are treated with a cocktail of polymeric micelles and TPGS/F127/P123 coupled with curcumin extracted from Curcuma longa [49].…”
Section: Various Natural Compoundsmentioning
confidence: 99%
“…Compounds 112, 126, and 140 showed significant cytotoxic activity against the A2780 human ovarian cancer cell line (IC 50 6.3±0.4, 1.10±0.05, and 1.3±0.1 µM, respectively) [15,51]. Recently, five prenylflavonoids, 6-prenylnaringenin (52), 7-O-methyl-6-prenylnaringenin (53), 4′-O-methyl-6prenylnaringenin (54), 7-O-methyl-8-prenylnaringenin (55), and 8-prenylnaringenin (59) obtained from M. conspurcatus exhibited cervical cancer (HeLa) cells with IC 50 values ranging from 10.08 to 60.16 µM [29].…”
Section: Cytotoxic and Antitumor Activitiesmentioning
confidence: 99%